(untitled) (Journal Of Educational and Psychological Researches, 2012)
Human beings are under the threat of the environment they are living in. With the course of time, they seriousness of this threat and its effect in changing their life . The most common threat that human beings might pass through is the trauma which is commonly bound with wars. The greater trauma that human beings might have is the threatening sudden facing or death facing. Consequently there would be disorder especially War disorder. This Phenomenon is clearly observed in Iraqi society as Iraq has been passing through continuous wars and disasters namely during and after the American Invasion. These events might lead to changes in Peoples behavior and to Social Violence. Thus, the Study aims at: • Exposing secondary School students with(PTSD). • Measuring(PTSD)of secondary School students. • Uncovering moral differences in (PTSD)according to sex variable(male-female). • Measuring Violence level of students suffering from(PTSD). • Uncovering moral differences in Violence of students with (PTSD)according to sex variables(male-female). • disclosing the nature of connectivity between the two variables of the study. In order to achieve these aims, the researcher adopts two scales: • (PTSD)scale: the researcher adopts standards of American World Society of Psychotherapy 4rth. Revision (DSM-IV-1994).It consists of two aspects: First, diagnostic aspect to Know wither the student had a trauma or not; Second, measurement aspect; this aspect comprise, five aspects-permanent agitation, incident feedback, emotions weak Nell, and social skill decreasing. These aspects comprise the whole scale measurement. • Violence scale: the researcher depends upon some literature in the light of which two measurement domains are pointed out: the physical Violence andante-properties Violence. The Final form of the scale comprise 32items specie find for those students afflicted and affected by (PTSD). Through the use of this scale, some Psychometric characteristics are achieved sush as content sincerity and external sincerity achieved through 80%and over agreement among experts. The researcher also depends on the internal connectivity matrix between the scale domains. In repeating test, the scale stability is achieved, since the stability of (PTSD)rate is 84% and Violence scale rate is 81%. This means that thy two scale are of high stability. After data verification statistically, it is concluded that: • (PTSD)rate is high. • There are moral difference in (PTSD)according to sex variable and for the sake of males. • The Violence rate due to (PTSD)is high. • there are Violence differences according to sex variable and for the sake of males. • There is a forward relation between (PTSD)and Violence of secondary school students. Throughout there results, some suggestions and advices are presented that might be of use to various social and educational Foundations.